Anti-glucocorticoid-induced Tumor Necrosis Factor–Related Protein (GITR) Therapy Overcomes Radiation-Induced Treg Immunosuppression and Drives Abscopal Effects - Schoenhals, Jonathan E.; Cushman, Taylor R.; Barsoumian, Hampartsoum B.; Li, Ailin; Cadena, Alexandra P.; Niknam, Sharareh; Younes, Ahmed I.; Caetano, Mauricio da Silva; Cortez, Maria Angelica; Welsh, James W. (Frontiers in Immunology, 2018)
Despite the potential to cure metastatic disease, immunotherapy on its own often fails outright or early on due to tumor immune evasion. To address this obstacle, we investigated combinations of anti-GITR, anti-PD1 and radiation therapy (XRT) in our previously developed anti-PD1 resistant 344SQ non-small cell lung adenocarcinoma preclinical tumor model. We hypothesized that targeting multiple mechanisms of immune evasion with this triple therapy would lead to an enhanced tumor-specific immune response and improve survival more so than any mono- or dual therapy. In a two tumor 344SQR murine model, treatment with anti-GITR, anti-PD1 and XRT led to significantly improved survival and an abscopal response, with half of the mice becoming tumor free. These mice showed durable response and increased CD4+ and CD8+ effector memory on tumor rechallenge. Regulatory T cells (Tregs) expressed the highest level of GITR at the tumor site and anti-GITR therapy drastically diminished Tregs at the tumor site. Anti-tumor effects were largely dependent on CD4+ T cells and partially dependent on CD8+ T cells. Anti-GITR IgG2a demonstrated superior efficacy to anti-GITR IgG1 in driving antitumor effects. Collectively, these results suggest that combinatorial strategies targeting multiple points of tumor immune evasion may lead to a robust and lasting antitumor response.